2012
DOI: 10.1149/2.054208jes
|View full text |Cite
|
Sign up to set email alerts
|

A Microelectrochemical System for In Situ High-Resolution Optical Microscopy: Morphological Characteristics of Pitting at MnS Inclusion in Stainless Steel

Abstract: A microelectrochemical system for in situ high-resolution optical microscopy was fabricated and applied to the real-time observation of pit initiation at MnS inclusion in type 304 stainless steel in NaCl solutions. It was directly observed that the metastable and stable pits were initiated at the MnS/steel boundaries, and that deep trenches were generated at these boundaries during anodic polarization. The initial rounded form of metastable and stable pits became polygonal in shape within 1 s. After that, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
138
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 36 publications
2
138
0
1
Order By: Relevance
“…For the solution-treated specimen, many current spikes were generated above 0.4 V, and the current density rapidly increased and exceeded 0.1 A m −2 at 0.67 V. The potential region for MnS dissolution has been reported to be around 0.5 V in NaCl solutions. 13,14,[17][18][19]24 The many current spikes around 0.5 V were due to the dissolution of the sulfide inclusions, suggesting that the inclusions were likely the initiation sites for pitting. 17 In the case of the sensitized specimen, a sharp increase in the current density appeared suddenly at 0.32 V. The pitting potential of the sensitized specimens were determined to be around 0.3 V.…”
Section: Resultsmentioning
confidence: 99%
“…For the solution-treated specimen, many current spikes were generated above 0.4 V, and the current density rapidly increased and exceeded 0.1 A m −2 at 0.67 V. The potential region for MnS dissolution has been reported to be around 0.5 V in NaCl solutions. 13,14,[17][18][19]24 The many current spikes around 0.5 V were due to the dissolution of the sulfide inclusions, suggesting that the inclusions were likely the initiation sites for pitting. 17 In the case of the sensitized specimen, a sharp increase in the current density appeared suddenly at 0.32 V. The pitting potential of the sensitized specimens were determined to be around 0.3 V.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows XPS narrow spectrums of each element after 2592 ks ( A schematic outline of the corrosion and dissolution of aluminum with the added metal cations is shown in Figure 9. Chiba et al investigated initial site for pitting corrosion of type 304 stainless steel by microelectrochemical system and reported that stable and meta-stable pitting events initiated at substrate and MnS boundaries [30]. By the SEM-EDS analysis (Figure 10), Mg-Si-Al related precipitates are observed, and in between these precipitates and the aluminum substrate there are areas where corrosion preferentially may occur, because no continuous oxide films may be formed, and aluminum may be preferentially dissolved here.…”
Section: Xps Analysismentioning
confidence: 99%
“…Anodic polarization measurements of the specimens with an exposed area of around 1 cm 2 indicated an increase in the pitting corrosion potential of the carburized stainless steels with interstitial carbon compared to untreated stainless steels. 1,[3][4][5] The microscopic anodic polarization measurements of the carburized stainless steel with a micro-scale electrode area (around 150 μm × 300 μm) containing an MnS inclusion, which is known to act as an initiation site of the pitting of stainless steels, [10][11][12][13][14][15][16][17][18][19][20][21] demonstrated that no pitting was initiated on the carburized stainless steel despite the presence of the MnS inclusion. 6 The micro-scale electrode areas were in situ observed by an optical microscope with a water immersion objective lens (a lateral resolution of ca.…”
mentioning
confidence: 99%
“…6 The micro-scale electrode areas were in situ observed by an optical microscope with a water immersion objective lens (a lateral resolution of ca. 350 nm) 19,22 during the microscopic anodic polarization. The microscopic polarization measurements revealed that the carburized stainless steel prevented the MnS inclusions from acting as pit initiation sites in chloride-containing environments, whereas pits were initiated at the MnS/steel boundaries on the untreated stainless steels.…”
mentioning
confidence: 99%